A novel cuproptosis-related diagnostic gene signature and differential expression validation in atherosclerosis - Yuting Cui; Yanyu Chen; Ni Gan; Man Li; Wei Liao; Yating Zhou; Qiong Xiang; Xi Gong; Qianqian Guo; Pengwei Hu; Xi-Long Zheng; Desi Shang; et al. (Molecular Biomedicine, 2023)
Abstract Atherosclerosis (AS) is a major contributor to morbidity and mortality worldwide. However, the molecular mechanisms and mediator molecules involved remain largely unknown. Copper, which plays an essential role in cardiovascular disease, has been suggested as a potential risk factor. Copper homeostasis is closely related to the occurrence and development of AS. Recently, a new cell death pathway called cuproptosis has been discovered, which is driven by intracellular copper excess. However, no previous studies have reported a relationship between cuproptosis and AS. In this study, we integrated bulk and single-cell sequencing data to screen and identify key cuproptosis-related genes in AS. We used correlation analysis, enrichment analysis, random forest, and other bioinformatics methods to reveal their relationships. Our findings report, for the first time, the involvement of cuproptosis-related genes FDX1, SLC31A1, and GLS in atherogenesis. FDX1 and SLC31A1 were upregulated, while GLS was downregulated in atherosclerotic plaque. Receiver operating characteristic curves demonstrate their potential diagnostic value for AS. Additionally, we confirm that GLS is mainly expressed in vascular smooth muscle cells, and SLC31A1 is mainly localized in macrophages of atherosclerotic lesions in experiments. These findings shed light on the cuproptosis landscape and potential diagnostic biomarkers for AS, providing further evidence about the vital role of cuproptosis in atherosclerosis progression.